Dietary inorganic phosphorus and intestinal peptide absorption - Hiroko Segawa; Junya Furutani; Ken-ichi Miyamoto (The Korean Society of Nephrology, 2012)
Both organic and inorganic phosphorus (Pi) are present in regularly consumed foods such as meats, eggs, and dairy products. Pi is often included in foods as an additive, as hidden phosphorus. The intestinal peptide transporter PepT1 mediates protein absorption, which is disturbed in renal insufficiency. In the present study, we examined the effects of dietary Pi content on the intestinal peptide transport activity and expression of PepT1. The following animal models were used: 1) 7-week-old, male Wistar rats; and 2) rats that underwent 3/4 nephrectomy (3/4NR) to induce chronic kidney disease (CKD). Rats were fed a normal-protein (20%) diet containing low (0.02%), normal (0.6%) or high (1.2%) Pi levels. Rats were also fed diets containing varying amounts of protein and either low or normal Pi levels, as follows: 1) low Pi/normal protein, 2) low Pi/high (50%) protein, 3) normal Pi/normal protein, and 4) normal Pi/high protein. Intestinal peptide transport activity and PepT1 expression levels were significantly higher in CKD rats than in sham-operated controls. Compared with the normal diet, the high-protein diet increased PepT1 expression in CKD rats. Intestinal di-peptide transport activity and PepT1 protein levels did not increase in rats fed the low-Pi/high-protein diet. In contrast, intestinal di-peptide transport activity and PepT1 protein expression were markedly increased in rats fed the normal-Pi/high-protein diet. In conclusion, dietary Pi levels regulate intestinal peptide transport activity via PepT1.